The cage of dark hours - Lostetter, Marina J. (Lostetter, Marina J. Five penalties, 2023)
"The Cage of Dark Hours is the second novel in the epic fantasy trilogy from acclaimed author Marina Lostetter, where the defeat of a serial killer back from the dead has pulled the mask off the myths and magics of a fantastical city. Krona and her Regulators survived their encounter with Charbon, the long-dead serial killer who returned to their city, but the illusions of their world were shattered forever. Allied with the healer Melanie they will battle the elite who have ruled their world with deception, cold steel, and tight control of the magic that could threaten their power, while also confronting beasts from beyond the foggy barrier that binds their world. Now they must follow every thread to uncover the truth behind the Thalo, once thought of as only a children's tale, who are the quiet, creeping puppet masters of their world. The Five Penalties Series: The Helm of Midnight The Cage of Dark Hours"--